ANALISIS BIROKRASI PELAYANAN PUBLIK PEMBUATAN AKTE KELAHIRAN PADA KANTOR PELAYANAN TERPADU (KPT) KOTA PEKANBARU - ', Mayarni (Universitas Riau, 2010)
The service was a duty that must be done by a official government as a society officer. Kantorpelayanan terpadu (kpt) in pekanbaru city is was built for giving public services that has good quality, fastservice beuracracy and cheap. This article try to explain about the public service in making birth certificateand analyze the barrier sectors at Kantor Pelayanan Terpadu (KPT) in pekanbaru city. This article showsthat the public services at Kantor Pelayanan Terpadu (KPT) in pekanbaru is not good enough. It can beknown from the unfinished birth certificate in time exactly, uncovenience situation because of the unsuretime and unfriendly officer in serving.